Консенсус еліт як умова конституцієтворення в Україні - Мандзій, Любомира (Lviv Polytechnic National University, 2015)
Розглянуто консенсус еліт як умову процесу конституційного творення в Україні. Виділено чотири періоди конситуцієтворення в Україні, докладно проаналізовано умови прийняття Конституції та внесення змін до Основного Закону в кожному періоді зокрема. In this article author examines elite consensus as a process condition of the constitutional creation in Ukraine. She selects four periods of constitutional process in Ukraine and analyzes in detail the conditions of acceptance of the Constitution and Amendments to the Basic Law in each period in particular.
Elite consensus as a condition for constitutional process in Ukraine
Keywords: Конституція; консенсус еліти; парламент; Президент; Constitution; elite consensus; parliament; president